LOW ASSOCIATION OF Bph17 ALLELE IN LANDRACES AND IMPROVED VARIETIES OF RICE RESISTANT TO BROWN PLANTHOPPER - Wage Ratna Rohaeni; Untung Susanto; Aida F.V. Yuningsih (Indonesian Agency for Agricultural Research and Development, 2017)
Resistance traits to brown planthopper on rice varieties are controlled by dominant and recessive genes called Bph/bph. Bph17 is one of dominant genes that control rice resistance to brown planthopper. Marker of Bph17 allele can be used as a tool of marker assisted selection (MAS) in breeding activity. Association of Bph17 allele and resistance to brown planthopper in Indonesian landraces and new-improved varieties of rice is not clearly known. The study aimed to determine the association of Bph17 allele in landraces and new-improved varieties of rice resistant to brown planthopper. Twenty-one rice genotypes were used in the study, consisting of 13 landraces, 5 improved varieties, 3 popular varieties and a check variety Rathu Heenati. Two simple sequence repeat markers linked to Bph17 allele were used, i.e. RM8213 and RM5953. The results showed that association of Bph17 allele in landraces and new-improved varieties of rice resistant to brown planthopper resistance was very low (r = -0.019 and -0.023, respectively). The presence of Bph17 allele did not constantly express resistance to brown planthopper. The study suggests that Bph17 allele cannot be used as a tool of MAS for evaluating resistance of landraces and new-improved varieties of rice to brown planthopper. Further research is needed to obtain a specific gene marker that can be used as a tool of MAS and applicable for Indonesian differential rice varieties.